Supplying the energy demand in the chicken meat processing poultry with biogas - Ferrarez, Adriano Henrique; Oliveira, Delly Filho; de Lacerda, Adílio Flauzino [UNESP]; Costa, José Márcio; Aparisi, Fabrício Segui (Universidad Nacional de Colombia, 2016)
The main use of electrical energy in the chicken meat processing unit is refrigeration. About 70% of the electricity is consumed in the compressors for the refrigeration system. Through this study, the energetic viability of using biogas from poultry litter in supplying the demand for the refrigeration process was found. The meat processing unit studied has the potential to process about a hundred and sixty thousand chickens a day. The potential biogas production from poultry litter is 60,754,298.91 m3.year-1. There will be a surplus of approximately 8,103 MWh per month of electric energy generated from biogas. An economic analysis was performed considering a planning horizon of 20 years and the discount rate of 12% per year. The economic analysis was performed considering scenario 1: sale of all electricity generated by the thermoelectric facility, and scenario 2: sale of the surplus electricity generated after complying with the demands of the refrigeration process and all other electrical energy and thermal energy use. Economic indicators obtained for scenarios 1 and 2 were favorable for the project implementation.
Suministro de la demanda de energía en el procesamiento de carne de pollo con biogás
Keywords: Ammonia absorption refrigeration; Distributed generation; Slaughterhouse; Waste of poultry